2010
DOI: 10.1523/jneurosci.2357-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Aβ Oligomers Cause Localized Ca2+Elevation, Missorting of Endogenous Tau into Dendrites, Tau Phosphorylation, and Destruction of Microtubules and Spines

Abstract: Aggregation of amyloid-␤ (A␤) and Tau protein are hallmarks of Alzheimer's disease (AD), and according to the A␤-cascade hypothesis, A␤ is considered toxic for neurons and Tau a downstream target of A␤. We have investigated differentiated primary hippocampal neurons for early localized changes following exposure to A␤ oligomers. Initial events become evident by missorting of endogenous Tau into the somatodendritic compartment, in contrast to axonal sorting in normal neurons. In missorted dendritic regions ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
485
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 588 publications
(525 citation statements)
references
References 67 publications
(80 reference statements)
37
485
1
2
Order By: Relevance
“…It has been reported that transfection of tau in mature neurons leads to an improper distribution of tau into the somatodendritic compartment with concomitant degeneration of synapses, as seen by the disappearance of spines and presynaptic and postsynaptic markers (3,7). In this study, there is a degeneration of synapses shown by synapsin I staining and dendritic spines in the deep layer of the PFC of PS1/APP doubletransgenic animals.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…It has been reported that transfection of tau in mature neurons leads to an improper distribution of tau into the somatodendritic compartment with concomitant degeneration of synapses, as seen by the disappearance of spines and presynaptic and postsynaptic markers (3,7). In this study, there is a degeneration of synapses shown by synapsin I staining and dendritic spines in the deep layer of the PFC of PS1/APP doubletransgenic animals.…”
Section: Discussionsupporting
confidence: 55%
“…Increasing evidence suggests that soluble amyloid ␤ peptide (A␤) is linked to hyperphosphorylation of tau at serine and threonine residues (5,6). A recent study has demonstrated that A␤ causes tau to wander into dendrites, leading to loss of synapses, spines, and microtubules (7)(8)(9). In 3xTg-AD mice harboring a knockin mutation for presenilin 1 (PS1, M146V) and transgenes for amyloid precursor protein (APPswe) and tau (tauP301L), spine loss occurs exclusively at dystrophic dendrites that accumulate both A␤ oligomers and hyperphosphorylated tau intracellularly (10), and it is the phosphorylation of tau that causes the protein to stray (11).…”
mentioning
confidence: 99%
“…6B). Importantly, these same pathways involving phospho-tau and caspase-3 previously were shown to be involved in oligomeric Aβ-induced abnormal excitability and synaptic spine loss (10,11,14,(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56). For example, the relatively specific inhibitor of caspase-3 activity, z-DEVD-fmk, blocks a pathway leading to dendritic spine shrinkage via activation of calcineurin, which results in dephosphorylation and internalization of synaptic AMPARs (56).…”
Section: Extrasynaptic Nmdars Mediate Aβ-induced Molecular Cascadesmentioning
confidence: 85%
“…causes a decay of dendritic spines mediated by Ca 2þ influx through NMDA receptors and thus a decay of neuronal communication (Fig. 4;Mattson 2004;Shankar et al 2007;Zempel et al 2010).…”
Section: Tau Protein In Neurofibrillary Degenerationmentioning
confidence: 99%
“…However, even with MTs the interaction is short-lived (dwell time 4s; Konzack et al 2007;Samsonov et al 2004), which explains why Tau can diffuse quite rapidly (diffusion constant D ¼ 3 mm 2 /s). This interaction is based on the repeats þ flanking domains, but can be interrupted by phosphorylation at key sites (e.g., KXGS motifs in repeats), which leads to the diffuse distribution of Tau in the cytosol and probably contributes to the somatodendritic missorting in degenerating neurons (Zempel et al 2010). Interactions of Tau with other cytoskeletal elements have been reported as well, notably intermediate filaments (Aamodt and Williams 1984) and microfilaments (F-actin; Griffith and Pollard 1978;Roger et al 2004).…”
Section: Fkbp52mentioning
confidence: 99%